Interactive Digital Storybook for Increasing Children Reading Interest of Indonesian Folklore - Mohammad Farid Naufal; Selvia Ferdiana Kusuma (Jurnal Informatika dan Multimedia, 2016)
Reading is very important for children but now children reading interest are decreasing, especially in Indonesian folklore. It happened because Indonesian folklore is written in traditional storybook version. If it continues to happen then children in the future will not know the histories of Indonesia. One way to increase children reading interest is introducing pictured storybook, but the traditional pictured storybook are not sufficient to increase children reading interest. In a growing era we can create a more interesting pictured storybook with implementing interactive digital storybook on android devices. Interactive means that children can interact to move the animated storybook characters. We assume that children interaction with interactive digital storybook can increase their enthusiasms in reading Indonesian folklore. To prove our hypothesis we conducted an experiment to 30 children. In the experiment, the children will read interactive digital storybook and traditional storybook after that we will see their responds. The result shows that interactive digital storybook can increase children reading interest of Indonesian folklore.